(3EOGQI GdCYeGd GdMchejIs - (3eMeO(B, (3GdUjQajs ((3GdGScfOQjI(B;(3GdbGgQI(B,(3WjHI ddfTQ hGdJhRjY(B:s (3MhQS GdOhdjI ddfTQ hGdJhRjY(B,s, 2005)
(3eGgjI heaghe GdGOGQI GdYGeI, GdJNWjW aj GdGOGQI GdYGeI, GdSjGSI GdYGeI, GdHjQhbQGWjI, GdJfXje aj GdGOGQI GdYGeI, GdefXeGJ GdYGeI, GdGOGQI GdeMdjI, GOGQI GdCaQGO aj GdefXeGJ GdYGeI(B.s
(3GdeQGLY U(B.335s
Keywords: (3EOGQI GdCYeGds; (3EOGQI GdCaQGOs; (3GdEOGQI GdYGeIs; (3GdJNWjWs